The Predictors of High Dietary Salt Intake among Hypertensive Patients in Iran - Parvin Reyhani; Fariba Azabdaftari; Mehrangiz Ebrahimi-Mamagani; Mohammad Asghari-Jafarabadi; Behjat Shokrvash (International Journal of Hypertension)
Background. Hypertension and its complications are among the major health problems all over the world, particularly in developing countries. The aims of this study were to show that, weather the hypertensive patients follow the expertise recommendations and differences between men and women in their levels of knowledge and behavior in salt taking. Methods. The present cross-sectional study was conducted among all hypertensive patients in rural health centers of Tabriz, Iran, in Feb–May; 2016. Data were collected by an interviewer-administrated questionnaire, along with anthropometric, blood pressure, and 24-hour urinary sodium excretion measurements. Multivariate logistic regression analysis was used to compute adjusted odds ratio (OR). Results. In all 205 patients, 62.9% female, 40.5% aged over 60 years, and 53.7% with low or moderate socioeconomic status, 49.3% body mass index (BMI) 30 kg/m2 and above, 10.2% of the patients had systolic/diastolic equal and above (≥) 40/90 mmHg, participated in the study. In total, 16.6% were aware of the daily salt allowance for healthy people with sex difference (P<0.001). Significant predictors of adding salt beyond the dietary recommendations in food preparation were occupation (unemployed) (OR = 4.05, 95% CI = 1.041–15.78, (P=0.044)) and blood pressure level (systolic/diastolic ≥140/90) (OR = 2.76, 95% CI = 1.28–5.96 (P=0.010)), while adding salt at the table correlated with sex (men) (OR = 4.47, 95% CI = 1.21–16.57 (P=0.025)), age (54–59) (OR = 0.05 95% CI = 0.01–0.39, (P=0.005)), and knowledge (general) (OR = 1.06, 95% CI = 0.99–1.13 (P=0.05)). Conclusion. The different pattern of salt intake was observed between men and women. In general, the amount of salt taken by hypertensive patients is higher than recommended allowances. Both men and women add extra amount of salt to food, women when preparing food and men at the table. Salt intake level both during preparing and eating food may be associated with occupation (unemployed), blood pressure level (systolic/diastolic ≥140/90), sex (men), age (54–59), and also patient knowledge (general).